Student’s Perception Regarding Quality of Public Service Marketing on Service Delivery - Palikhe, Amin; Bhandari, Rita; Phuyal, Shreeram; Paudel, Shiva Prasad Sharma (Kanya Journal, 2023)
Public Service Marketing has been used as game plan to enhance service delivery in the public sector. A gap has been seen in using quality service dimensions and public service marketing concept for enhancing service delivery in public sector. This study therefore assessed the citizen’s perception regarding the quality of public service marketing on service delivery in public sector of Nepal. Special references have been taken from students studying master degree in Management at Prithvi Narayan Campus, Pokhara. Descriptive and quantitative research design has been employed for this study. Out of 180 total populations under study, 50 samples have been taken by using simple random sampling. Data were collected via questionnaires using Google Form. Data were analyzed using SPSS 26 statistical tools. Quantitative statistical results were analyzed. The practical implications is to assess the perception of citizens i.e. students of master degree in this study towards quality service delivery and customer satisfaction. The study revealed that the perception of students towards quality service delivery and customer satisfaction is different among the groups but there have been positive impact of quality of public service marketing factors on service delivery with customer satisfaction. However, overall perception towards the service quality and satisfaction is not good. Additionally, easy access to service and good behaviors of employees in public sector were deemed to be essential for positive enhancement in citizen’s perceptions regarding the quality of public service marketing on service delivery. The study was limiting only two service delivery factors therefore, it will be recommended to study numerous additional influencing elements like cost, time and communication that can be used in research in future as quality of service delivery factors.